Polacy o aktywności kobiet w polityce. Czy należy wprowadzać dodatkowe mechanizmy zwiększające udział Polek w życiu politycznym? - Musiał-Karg, Magdalena (Political Preferences, 2014)
Without any doubt since 1989 one may observe increasing women's role in Polish political life. One of proofs for it is higher number of women registered as candidates before parliamentary elections, as well as higher percentage of women in Polish Sejm. In spite of this, Polish women are still less active in the political life than men, which results from existence of several barriers hindering their participation and involvement in politics. The main aim of this article is to analyze the opinion of Poles on the activity of women in political life and on the introduction of additional mechanisms having the potential to increase women's participation in political bodies.